2009
DOI: 10.1007/s00702-009-0207-z
|View full text |Cite
|
Sign up to set email alerts
|

The FGF-2/FGFRs neurotrophic system promotes neurogenesis in the adult brain

Abstract: Neurogenesis occurs in two regions of the adult brain, namely, the subventricular zone (SVZ) throughout the wall of the lateral ventricle and the subgranular zone (SGZ) of the dentate gyrus (DG) in hippocampal formation. Adult neurogenesis requires several neurotrophic factors to sustain and regulate the proliferation and differentiation of the adult stem cell population. In the present review, we examine the cellular and functional aspects of a trophic system mediated by fibroblast growth factor-2 (FGF-2) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(89 citation statements)
references
References 133 publications
1
86
0
2
Order By: Relevance
“…Third, a2-tancytes respond to elevated levels of FGF in vivo through enhanced proliferation. FGFs and FGF receptors have been described in other adult NSC niches, and are widely accepted to be potent modulators of progenitor cell proliferation, but in neither the SVZ nor the SGZ do they display a highly localised distribution 44,45 . The presence of endogenous Fgfs and evidence of the requirement for active growth factor signalling suggest that FGF signalling has a role in the control of a-tanyctes under normal conditions, perhaps limiting differentiation that might occur through localised CNTF 1,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Third, a2-tancytes respond to elevated levels of FGF in vivo through enhanced proliferation. FGFs and FGF receptors have been described in other adult NSC niches, and are widely accepted to be potent modulators of progenitor cell proliferation, but in neither the SVZ nor the SGZ do they display a highly localised distribution 44,45 . The presence of endogenous Fgfs and evidence of the requirement for active growth factor signalling suggest that FGF signalling has a role in the control of a-tanyctes under normal conditions, perhaps limiting differentiation that might occur through localised CNTF 1,46 .…”
Section: Discussionmentioning
confidence: 99%
“…The most interesting observation was the significant difference in the mean dialysate concentration of FGF2 in the oldest patients compared with that of other age groups. This was an unexpected finding since FGF2 is generally thought as having an important role in recovery from brain damage (Monfils et al, 2005;Mudò et al, (2009;Yoshimura et al, 2001). However, based on data from experimental stroke models, it has been proposed that the timing of the cellular and genetic response to cerebral insult is dysregulated in aged animals.…”
Section: Mellergå Rd Et Almentioning
confidence: 99%
“…Over ten growth factors and neurotrophins have been found to influence AHN. Fibroblast growth factor (FGF-2) and epidermal growth factor (EGF) are the primary mitogens used in vitro to propagate neural progenitor cells, and FGF-2 is hypothesized to play a permissive role in vivo in hippocampal progenitor cell proliferation [82]. Indeed, it has been found that deletion of fibroblast growth factor receptor-1 in the CNS decreases hippocampal progenitor cell proliferation [127].…”
Section: Extrinsic Factorsmentioning
confidence: 99%